2019
DOI: 10.1007/s10531-019-01781-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in biodiversity and climate change studies in India

Abstract: Biodiversity is continually transformed by a changing climate. Conditions change across the face of the planet at variable pace leading to rearrangements of biological associations. The carbon cycle and the water cycle, arguably the two most important large-scale processes for life on Earth; depend on biodiversity at genetic, species, and ecosystem levels and can yield feedbacks to climate change. India is no less affected through this feedback mechanism of climate change and had shown its cause and effect ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, the Himalayan ecosystems are highly vulnerable and are degrading due to various biotic and abiotic stresses (Wani et al, 2022). Overall, climate change is a leading cause of ecological changes and biodiversity loss, although species invasions are also one of the important factors contributing to changes in forest productivity and biodiversity loss, especially native and endemic species (Behera et al, 2019;Negi et al, 2021;Wani et al, 2021). Besides these factors, the forests of the Himalayan region are now becoming vulnerable due to increasing anthropogenic disturbances like deforestation, unsustainable fuel wood, timber collection, and agricultural expansion (Negi and Maikhuri, 2017;Thakur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Himalayan ecosystems are highly vulnerable and are degrading due to various biotic and abiotic stresses (Wani et al, 2022). Overall, climate change is a leading cause of ecological changes and biodiversity loss, although species invasions are also one of the important factors contributing to changes in forest productivity and biodiversity loss, especially native and endemic species (Behera et al, 2019;Negi et al, 2021;Wani et al, 2021). Besides these factors, the forests of the Himalayan region are now becoming vulnerable due to increasing anthropogenic disturbances like deforestation, unsustainable fuel wood, timber collection, and agricultural expansion (Negi and Maikhuri, 2017;Thakur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the existing literature advocates that climate change in the anthropogenic era has a direct effect on biodiversity, forcing tree species to adapt either through migrating, developing new physiological traits, or changing phenological cycles (Behera et al, 2019). Higher tree species richness indicates a more stable ecosystem and may demonstrate a better ecosystem/carbon service (Ives et al, 2001).…”
Section: Discussion Tree Diversity In Different Land Usesmentioning
confidence: 99%
“…The major effects that cryospheric changes have on plants at species and ecosystem levels are changes in phenology, upslope habitat shifts, changes in structure of populations and communities, densification, growth enhancement, physiological changes, and changes in biochemical processes. Besides these, changes in soil stoichiometry characteristics (Zhang et al, 2019), increase in incidences of invasive alien species, species redundancy, and shift in dominance between species (Behera et al, 2019) are among the other impacts observed. In some cases, regions that were inhospitable due to colder climatic conditions at higher elevations have now become suitable for various monoculture plantations, which pose a threat to the habitats of endemic species through encroachment .…”
Section: Impacts On Biodiversity At Genetic Species and Ecosystem Levelsmentioning
confidence: 99%